An automated computational tool for drilling quality assurance and quality control in block caving mining - Henríquez, J.P.; Torres, C.; Morales, D. (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
Drilling quality control is a key factor in the performance of blasting and cave development in block caving operations. However, quality assurance and quality control (QA/QC) analysis of drilling data is often manual, time-consuming, and inconsistent – particularly when large datasets and multiple excavation stages are involved. This paper presents a computational tool, developed by Enaex’s underground team, for automated QA/QC analysis of drilling in block caving mines. The tool integrates real drilling data obtained from drilling rigs or borehole deviation measurement instruments and automatically compares them with the theoretical blast design using vector projection analysis. Key parameters such as inclination, bearing, collar position, hole length, and spatial deviation are evaluated. The system automatically generates graphical outputs and summary tables, including traffic-light alert indicators based on predefined tolerance criteria. In addition to drilling data, the tool allows the incorporation of pre-blast information, such as hole cleaning length and post-blast data – including actual explosive loading lengths. A distinctive capability of the tool is the extrapolation and triangulation of drilling data to generate threedimensional solids and volumes representing the effective blast geometry. This enables advanced pre- and post-blast analyses, such as verifying connectivity between undercut levels and drawbell, or identifying potential remnant pillars between parallel drifts in the undercut level due to undercut blasts. All analyses are performed automatically, significantly reducing processing time while improving consistency, engineering quality, and decision-making efficiency in block caving drilling QA/QC workflows.